Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3389/fnhum.2010.00206
|View full text |Cite
|
Sign up to set email alerts
|

Knowing beans: human mirror mechanisms revealed through motor adaptation

Abstract: Human mirror mechanisms (MMs) respond during both performed and observed action and appear to underlie action goal recognition. We introduce a behavioral procedure for discovering and clarifying functional MM properties: blindfolded participants repeatedly move beans either toward or away from themselves to induce motor adaptation. Then, the bias for perceiving direction of ambiguous visual movement in depth is measured. Bias is affected by (a) number of beans moved, (b) movement direction, and (c) similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…We know this in part from findings that perceptual and motor information comes online very early—as quickly as 100 ms from word onset (Amsel, Urbach, & Kutas, ; Pulvermuller, Shtyrov, & Hauk, ). The causal function of these activations is further supported by studies showing that disrupting perceptual or motor resources decreases comprehension speed (Glenberg et al., ; Pulvermüller, Shtyrov, & Ilmoniemi, ) and accuracy (Yee, Chrysikou, Hoffman, & Thompson‐Schill, ) of words whose meanings involve those specific percepts or actions.…”
Section: Language Programs the Mind By Interfacing With Grounded Mentmentioning
confidence: 81%
“…We know this in part from findings that perceptual and motor information comes online very early—as quickly as 100 ms from word onset (Amsel, Urbach, & Kutas, ; Pulvermuller, Shtyrov, & Hauk, ). The causal function of these activations is further supported by studies showing that disrupting perceptual or motor resources decreases comprehension speed (Glenberg et al., ; Pulvermüller, Shtyrov, & Ilmoniemi, ) and accuracy (Yee, Chrysikou, Hoffman, & Thompson‐Schill, ) of words whose meanings involve those specific percepts or actions.…”
Section: Language Programs the Mind By Interfacing With Grounded Mentmentioning
confidence: 81%
“…This can potentially be addressed using priming or adaptation paradigms (Henson and Rugg, 2003; Wheatley et al, 2005; Gold et al, 2006). Recent studies have introduced motor priming paradigms to the investigation of embodiment (Glenberg et al, 2010). In a recent combined EEG/MEG study, arm- and leg-related words were presented shortly after participants initiated the experimental trial themselves by button press (Mollo et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…These electrophysiological studies suggested that an activation of sensorimotor areas is connected to concrete action language processing. A great number of behavioral and fMRI studies further supported this assumption (D'Ausilio et al, 2009;Glenberg et al, 2010;Hauk et al, 2004;Klatzky, Pellegrino, McCloskey, & Doherty, 1989;Moseley & Pulvermüller, 2014;Pulvermüller, Shtyrov, & Ilmoniemi, 2005) and partly revealed that processing abstract action language (e.g., pushing the argument) leads to an activation of motor areas as well (Desai, Binder, Conant, Mano, & Seidenberg, 2011;Desai, Conant, Binder, Park, & Seidenberg, 2013;Glenberg et al, 2008;Romero Lauro, Mattavelli, Papagno, & Tettamanti, 2013;Schaller, Weiss, & Müller, in press;Wilson & Gibbs, 2007). However, the effects following abstract action language seem to be weaker than those following concrete action language.…”
Section: Introductionmentioning
confidence: 92%